Stereoselective Pd-catalyzed etherification and asymmetric synthesis of furanomycin and its analogues from a chiral aziridine1. Issue 30 (14th August 2015) - Jung, Jae-Hoon; Yoon, Doo-Ha; Lee, Kyuwoong; Shin, Hyeonah; Lee, Won Koo; Yook, Cheol-Min; Ha, Hyun-Joon
<x xml:space="preserve">Abstract</x> A chiral aziridine was utilized for the synthesis of the anti-bacterial natural amino acid l-(+)-furanomycin, and its analogues including 5′-epi-furanomycin and norfuranomycin.